Human Nutrition A Health Perspective - Barasi, Mary E. (London : Arnold, 1997)
This text introduces the reader to nutritional theory, and by considering everyday eating practice, applies this to the maintenance of health and prevention of disease.
Includes bibliographical references and index.
Keywords: Nutrition; Nutrition -- Requirements; Nutrition counseling -- Great Britain; Health and Fitness